EFEKTIFITAS BERMAIN FINGER PAINTING UNTUK MENINGKATKAN KEMAMPUAN SENI MENGGAMBAR PADA ANAK USIA DINI KELOMPOK B DI TK GIRI KUSUMA DESA PELAGA TAHUN 2020 - Nariani Ni Nyoman; Sudarsana I Ketut; Budiasih Ni Wayan (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
The art of drawing is an activity of designing, creating, and exploring which includes creating works of art such as painting and drawing. To improve children's abilities through playing finger painting is not easy. Because not all children in group B at Kindergarten Giri Kusum can draw. This is Anther's challenge for researchers to research on improving children's learning abilities through classroom action in the Effectiveness of Playing Finger Painting to Improve the Art Ability of Early Childhood Drawing in Group B at Kindergarten Giri Kusuma, Pelaga Village in 2020. The problems discussed in this study are: To what extent is the effectiveness of playing finger painting in early childhood group B in TK Giri Kusuma, Pelaga village, Kec. Evening, Kab. Badung in 2020 in improving your art drawing skills? The purpose of this study was to improve the ability to draw early childhood group B through finger painting at TK Giri Kusuma, Pelaga Village. The theories used to support this research are (1) cognitive theory from Jean Piaget, (2) group learning theory from Abu Ahmadi (2004), and (3) behaviorism theory from Arya (2010). The subjects of this study were group B early childhood at Kindergarten Giri Kusuma Pelaga Village in 2020. With the research object, the students' ability to adjust the colors on the available image media. Data collection methods used are observation, interviews, literature, and documentation. The research instrument was an observation sheet. The data analysis technique in this research uses descriptive quantitative research, where the researcher describes/explains the observation data in the form of the acquisition of numbers. The results of this study indicate, the overall value before the action (not using finger painting) is 117 with an average value of 8.36, of which 12 children have not reached 50%, namely 41.78%. And after the action (after using finger painting) the percentage value reached 82.14%. The value obtained is 230 with an average value of 16.43 all children are well creative, without burden, and according to expectations. From this explanation, it can be concluded that the effectiveness of playing finger painting can improve the ability to draw early childhood group B in TK Giri Kusuma, Pelaga Village in 2020.